Competição e persistência populacional em Acanthoscelides macrophthalmus: uma análise de estrutura populacional - Iano, Daniela Mayumi [UNIFESP] (2018)
The understanding of how variations in demographic processes directly influence population dynamics and persistence has been the focus of ecology for many years. It is already known that competition is one of the ecological interactions that most interfere in the biological parameters and in the abundance of the species. In this study, we have investigated how larval competition may affect the structure and population persistence of Acanthoscelides macrophthalmus, as well as its interference with the finite rate of population increase and the contribution of dispersion to the persistence of this species. Mature fruits of the host plant Leucaena leucocephala were collected from a population located in São Paulo, SP. The fruits were taken to the laboratory where they were dissected. The seeds were conditioned in six transparent plastic containers and the second generation of bruchine was established as a control population. Seeds with one or two eggs were individualized, and two treatments were established: 1) seeds without larval competition and 2) seeds with larval competition. The seeds containing eggs were individualized, and after five days 20 seeds per treatment were dissected every two days to remove the larvae. After that, the cephalic capsule of each larva was measured. The population structure was determined through the elaboration of projection matrices, from which the finite rate of increase (R), the stable distribution of stages, the sensitivity and the elasticity were estimated. Considering a single population, the simulations were done to calculate the population persistence time and the proportion of occupied patches adding 0, 5, and 10% of migration. The finite rate of population growth (R) was higher for the treatment without competition. Competition also reduced the body size of third instar larva and sensitivity results showed that the transition from the third to the fourth instar was the most important for R estimation, suggesting that this stage was mostly affected by competition. The stable stage distribution showed that the probability of populations being extinct is higher when competition is present. It was observed that competition should occur at high rates in populations to produce a significant decrease in R. Populations showed high levels of persistence (for 100 generations), even with competition, and only 5% of migration increased the persistence of populations.